Urological Cancers in Clinical Practice - Waxman, Jonathan.; Waxman, Jonathan. (Springer London : Imprint: Springer, 2007)
Urological oncology constitutes 20% of all malignant disease, and includes renal, bladder, prostate and testicular cancer. This is an area of medical and scientific interest, where advances in clinical practice and translational research have led to significant changes in the way that patients are managed. The book summarizes developments in all areas of urological cancer. The aim of the book is to educate urologists and oncologists so that they are able to understand scientific developments within urological oncology and be up to date with clinical practice in this area. The book provides a guide for clinical practice. This practical handbook provides a distillation of current practice for oncologists and urologists in clinical practice.